SISTEM PENJAMINAN MUTU INTERNAL (SPMI) DALAM PENDIDIKAN ISLAM : ANALISIS KONSEPTUAL DAN TANTANGAN IMPLEMENTASI - Dayanti, Reski; Julaiha, Siti; Yamani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Internal Quality Assurance System (SPMI) plays an essential role in maintaining and improving the quality of higher education, including within the context of Islamic education. This study aims to examine the basic concept of SPMI, its principles and components, its implementation in Islamic education, as well as the challenges and strategies for its strengthening. This research employs a qualitative approach using library research with a descriptive-analytical method. The findings indicate that, conceptually, SPMI has been well designed through the PPEPP cycle. However, its implementation still faces several challenges, particularly in structural, cultural, and technical aspects. A case study at SMP IT Insan Mulia shows that the main issue does not lie in the absence of the system, but rather in the lack of a strong quality culture. Therefore, strengthening SPMI should focus on transforming organizational culture and integrating Islamic values into quality assurance practices.